Phenylketonuria incidence in China between 2013 and 2017 based on data from the Chinese newborn screening information system: a descriptive study. Issue 8 (22nd August 2019) - Xiang, Liangcheng; Tao, Jing; Deng, Kui; Li, Xiaohong; Li, Qi; Yuan, Xuelian; Liang, Juan; Yu, Erling; Wang, Meixian; Wang, Huiqing; Liu, Hanmin; Zhu, Jun
Abstract : Objective: This study examines the incidence and spatial clustering of phenylketonuria (PKU) in China between 2013 and 2017. Methods: Data from the Chinese Newborn Screening Information System were analysed to assess PKU incidence with 95% CIs by province, region and disease severity. Spatial clustering of PKU cases was analysed using global and local spatial autocorrelation analysis in the geographic information system. Results: The database contained 4925 neonates with confirmed PKU during the study period, corresponding to an incidence of 6.28 (95% CI: 6.11 to 6.46) per 100 000 neonates screened. Incidence was highest in the provinces of Gansu, Ningxia and Qinghai, where it ranged from 19.00 to 28.63 per 100 000 neonates screened. Overall incidence was higher in the northern part of the country, where classical disease predominated, than in the southern part, where mild disease predominated. PKU cases clustered spatially (global Moran's I=0.3603, Z =5.3097, p<0.001), and local spatial autocorrelation identified four northern provinces as high–high clusters (Gansu, Qinghai, Ningxia and Shanxi). Conclusions: China shows an intermediate PKU incidence among countries, and incidence differs substantially among Chinese provinces and between northern and southern regions. Our results suggest the need to focus efforts on screening, diagnosing and treating PKU in high-incidence provinces.